2014
DOI: 10.1186/1472-6882-14-76
|View full text |Cite
|
Sign up to set email alerts
|

Paederia foetida Linn. leaf extract: an antihyperlipidemic, antihyperglycaemic and antioxidant activity

Abstract: BackgroundThe primary objective of the present investigation is to evaluate the antidiabetic, antihyperlidemic and antioxidant activity of the methanolic extract of the Paederia foetida Linn. (PF) leaf extract in the streptozotocin induced diabetic rats.MethodsSingle intraperitoneal injection (IP) of streptozotocin (60 mg/kg body weight) was used for induction of diabetes is swiss albino (wistar strain) rats. The induction of diabetes was confirmed after 3 days as noticing the increase in blood sugar level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 52 publications
3
37
0
3
Order By: Relevance
“…Hence, the present study concludes that even the leaves of micropropagated P. foetida can be used as a source of lead Oral administration of different doses (100, 250, and 500 mg) of methanolic leaf extracts of naturally grown P. foetida significantly improved the level of superoxide dismutase, catalase, and glutathione peroxidase in induced diabetic group of rats [3]. Hence, antioxidant treatment may be beneficial for diabetic patient, and P. foetida plant will be a major help in this regard [3]. Antioxidant potential by DPPH radical scavenging activity of methanolic leaf extracts of naturally grown P. foetida has also been reported by Nayak et al [19], and antioxidant activity by ABTS radical cation assay of the methanol extract of the whole plant of P. foetida has been reported by Osman et al [6].…”
Section: Antioxidant Studysupporting
confidence: 55%
See 2 more Smart Citations
“…Hence, the present study concludes that even the leaves of micropropagated P. foetida can be used as a source of lead Oral administration of different doses (100, 250, and 500 mg) of methanolic leaf extracts of naturally grown P. foetida significantly improved the level of superoxide dismutase, catalase, and glutathione peroxidase in induced diabetic group of rats [3]. Hence, antioxidant treatment may be beneficial for diabetic patient, and P. foetida plant will be a major help in this regard [3]. Antioxidant potential by DPPH radical scavenging activity of methanolic leaf extracts of naturally grown P. foetida has also been reported by Nayak et al [19], and antioxidant activity by ABTS radical cation assay of the methanol extract of the whole plant of P. foetida has been reported by Osman et al [6].…”
Section: Antioxidant Studysupporting
confidence: 55%
“…Cellular damage or oxidative injury arising from free radicals of ROS now appears to be one of the key factors for a number of human disease, such as inflammation, cancer, atherosclerosis, neurodegenerative disease, and aging [15,37]. Hence, the present study concludes that even the leaves of micropropagated P. foetida can be used as a source of lead Oral administration of different doses (100, 250, and 500 mg) of methanolic leaf extracts of naturally grown P. foetida significantly improved the level of superoxide dismutase, catalase, and glutathione peroxidase in induced diabetic group of rats [3]. Hence, antioxidant treatment may be beneficial for diabetic patient, and P. foetida plant will be a major help in this regard [3].…”
Section: Antioxidant Studymentioning
confidence: 53%
See 1 more Smart Citation
“…4, daily oral administration of IL8 sprout extracts for the 21 days of experimental period significantly improved plasma insulin levels and decreased blood glucose levels as compared to their seed extracts. In one of the recent studies, fenugreek seeds have been reported to significantly increase the reduced serum insulin levels of STZ-induced diabetic rats, via stimulation of insulin secretion and regeneration of the β-cells of the pancreas 25 . It is proposed that the possible antihyperglycemic mechanism involved by fenugreek sprout extracts may be either due to their insulin emission from the β-cells, followed by improved glucose transportation or consumption 26 .…”
Section: Fig5: Effect Of Il8 Sprout Extract Treatment On Liver Glycomentioning
confidence: 99%
“…Different doses of UFD were administered to the test groups in graded doses ranging up to 100 mg/kg. The animals were continuously observed for 2 h for the following (Kumar et al 2014;Ghosh 1984) 3. Autonomic profile: urination and defecation.…”
Section: Acute Toxicity Studymentioning
confidence: 99%